2005
DOI: 10.1177/1524838005280857
|View full text |Cite
|
Sign up to set email alerts
|

Responsivity Issues in the Treatment of Sexual Offenders

Abstract: Andrews and Bonta (2003) have presented a model of effective correctional programming focusing on risk, need, and responsivity factors for a general criminal population. When applied to sexual offenders, the first two issues (risk assessment and treatment targets such as cognitive distortions) have received a great deal of research attention. However, little attention has been paid to responsivity issues: those factors that influence the extent to which clients benefit, or fail to benefit, from treatment progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
13

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 106 publications
0
36
0
13
Order By: Relevance
“…Those working with child sexual abusers are faced with the challenge of providing effective treatment and assuaging public concern about safety. Over the past two decades, much research has focused on the assessment and treatment of sexual offenders in the UK, United States, Australia, and Canada (e.g., Abracen & Looman, 2004Chaffin, 1994;Eastman, 2004;Frost, 2004;Houston, Wrench, & Hosking, 1995;Jenkins-Hall, 1994;Kear-Colwell & Boer, 2000;Langton, Barbaree, Harkins, & Peacock, 2006;Levenson & Macgowan, 2004;Lindsay, Neilson, Morrison, & Smith, 1998;Looman, Dickie, & Abracen, 2005;MacDonald, 1994;Marshall, 1996;Marshall, Anderson, & Fernandez, 1999;Marshall, Jones, Ward, Johnston, & Barbaree, 1991;McGrath, Cumming, Livingston, & Hoke, 2003;Petersilia, 1990;Polizzi, MacKenzie, & Hickman, 1999;Raynor & Vanstone, 1997;Schofield, 1994;Schweitzer & Dyer, 2003;Seager, Jellicoe, & Dhaliwal, 2004;Shanahan & Donato, 2001). Yet debate persists as to the effectiveness of treatment in reducing recidivism (Brooks-Gordon et al, 2004;Hanson et al, 2002;Matthews & Pitts, 1998;Schweitzer & Dwyer;Seager et al, 2004;Terry & Mitchell, 2001).…”
Section: Previous Research On Treatment Programsmentioning
confidence: 98%
“…Those working with child sexual abusers are faced with the challenge of providing effective treatment and assuaging public concern about safety. Over the past two decades, much research has focused on the assessment and treatment of sexual offenders in the UK, United States, Australia, and Canada (e.g., Abracen & Looman, 2004Chaffin, 1994;Eastman, 2004;Frost, 2004;Houston, Wrench, & Hosking, 1995;Jenkins-Hall, 1994;Kear-Colwell & Boer, 2000;Langton, Barbaree, Harkins, & Peacock, 2006;Levenson & Macgowan, 2004;Lindsay, Neilson, Morrison, & Smith, 1998;Looman, Dickie, & Abracen, 2005;MacDonald, 1994;Marshall, 1996;Marshall, Anderson, & Fernandez, 1999;Marshall, Jones, Ward, Johnston, & Barbaree, 1991;McGrath, Cumming, Livingston, & Hoke, 2003;Petersilia, 1990;Polizzi, MacKenzie, & Hickman, 1999;Raynor & Vanstone, 1997;Schofield, 1994;Schweitzer & Dyer, 2003;Seager, Jellicoe, & Dhaliwal, 2004;Shanahan & Donato, 2001). Yet debate persists as to the effectiveness of treatment in reducing recidivism (Brooks-Gordon et al, 2004;Hanson et al, 2002;Matthews & Pitts, 1998;Schweitzer & Dwyer;Seager et al, 2004;Terry & Mitchell, 2001).…”
Section: Previous Research On Treatment Programsmentioning
confidence: 98%
“…Despite these successes and others like them, some researchers have highlighted the shortcomings of the RNR model in terms of the absence of a group work delivery model. Several authors (Harkins & Beech, 2007;Looman, Dickie, & Abracen, 2005;Ogloff & Davis, 2004;Ross, 2008;Ward & Stewart, 2003) have suggested that the RNR model's focus on risk management and relapse prevention has influenced a de-emphasis on the responsivity principle. This has diverted attention from process factors and led to an over-reliance on manualized content.…”
Section: A Review Of the Creative Group Work Training Program For Facmentioning
confidence: 98%
“…Traditional cognitive-behavioral therapy (CBT) techniques are employed widely throughout the corrections system to restructure the thoughts and subsequent actions of offenders by teaching more effective methods of thinking and coping (Spiegler & Guevremont, 2010 ). By focusing on dynamic risk factors like sexual deviance, antisocial orientation and intimacy defi cits (Hanson & Morton-Bourgon, 2005 ), and making adaptations to account for the client's learning style, cultural background, and level of motivation (Langevin & Curnoe, 2007 ), modern rehabilitative practices are gaining a great deal of support (Hanson et al, 2002 ;Looman et al, 2005 ;Lösel & Schmucker, 2005 ;McGrath, Cumming, Livingston, & Hoke, 2003 ;McGrath, Hoke, & Vojtisek, 1998 ;Scalora & Garbin, 2003 ).…”
Section: Reform Of Current Lawsmentioning
confidence: 99%